Single-incision laparoscopic totally extraperitoneal inguinal hernia repair with tumescent local anesthesia: report of more than 2000 procedures at a day-surgery clinic - Wakasugi, Masaki; Hasegawa, Junichi; Ikeda, Yoshihiro (Surgery today (Tokyo, Japan), 2021)
Purpose The purpose of this study was to evaluate the feasibility and safety of single-incision laparoscopic surgery for totally extraperitoneal inguinal hernia repair (SILS-TEP) with tumescent local anesthesia (TLA) at a day-surgery clinic. Methods We analyzed, retrospectively, 2148 patients who underwent SILS-TEP under general anesthesia with TLA between April, 2015 and March, 2020 at Gi surgical clinic, to evaluate their operative outcomes. The TLA agent, consisting of normal saline and lidocaine with epinephrine and ropivacaine, was injected during surgery. Results The median operative times for unilateral and bilateral hernia were 50 min and 75 min, respectively. Blood loss was minimal in all patients. Conversion to the Lichtenstein method was required in 4% (91/2148) of patients. The median recovery room stay was 125 min and no analgesics were required in the recovery room by 75% (1613/2148) of the patients. All the patients left the clinic on the day of surgery. Complications developed in 6.5% (139/2148) of the patients, as seromas in 6% (125/2148), wound infections in 0.4% (8/2148), and hematomas in 0.2% (4/2148), respectively. Bowel injury and obstruction each occurred in 0.05% (1/2148) of the patients. There were no hernia recurrences. Conclusion SILS-TEP with TLA can be performed safely at a day-surgery clinic.